2015
DOI: 10.1111/cas.12754
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic pre‐B cell leukemia transcription factor interacting protein is overexpressed in gastric cancer and promotes gastric cancer cell proliferation, migration, and invasion

Abstract: Hematopoietic pre-B cell leukemia transcription factor interacting protein (HPIP) has been shown to play an important role in the development and progression of some cancers. However, the role of HPIP in gastric cancer (GC) is unclear. Here, we show that HPIP is upregulated in most GC patients and promotes GC cell proliferation, migration, and invasion. In GC patients, HPIP positively associates with tumor size and nodal metastasis, and negatively associates with tumor differentiation. Hematopoietic pre-B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…HPIP has been reported to be overexpressed in many types of cancers, including colorectal cancer (15), astrocytoma (16), thyroid carcinoma (17), breast cancer (18), non-small cell lung cancer (19) and hepatocellular carcinoma (20), and plays an important role in the development and progression of these tumors. In GC, the expression of HPIP was found to be significantly upregulated in tumors compared with that noted in adjacent normal tissues and was found to be positively correlated with tumor size and metastasis (21). HPIP overexpression was found to increase GC cell proliferation by promoting cell cycle progression and to enhance GC cell migration by modulating epithelial-mesenchymal transition (EMT) (21).…”
Section: Introductionmentioning
confidence: 99%
“…HPIP has been reported to be overexpressed in many types of cancers, including colorectal cancer (15), astrocytoma (16), thyroid carcinoma (17), breast cancer (18), non-small cell lung cancer (19) and hepatocellular carcinoma (20), and plays an important role in the development and progression of these tumors. In GC, the expression of HPIP was found to be significantly upregulated in tumors compared with that noted in adjacent normal tissues and was found to be positively correlated with tumor size and metastasis (21). HPIP overexpression was found to increase GC cell proliferation by promoting cell cycle progression and to enhance GC cell migration by modulating epithelial-mesenchymal transition (EMT) (21).…”
Section: Introductionmentioning
confidence: 99%
“…We also exemplified our hypothesized mechanism by an H3K36me3-associated isoforms switch of PBX1. In addition to its well-known functions in lymphoblastic leukemia (Kamps and Baltimore 1993;Foa et al 2000;Tesanovic et al 2014;Melendez et al 2015) and a number of cancers (Berge et al 2006;Qiu et al 2007;Park et al 2008;Magnani et al 2011;Thiaville et al 2012;Li et al 2014;Feng et al 2015;Jung et al 2015;Magnani et al 2015;Jung et al 2016), PBX1 was also found to promote hESC self-renewal by corporately binding to the regulatory elements of NANOG with KLF4 (Chan et al 2009). We found that the transcriptions of two isoforms of PBX1, PBX1a and PBX1b, are putatively regulated by H3K36me3 during hESC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…PBX1 was one of the genes that their ASs are positively associated with H3K36me3 ( Figures 5A, B). Its protein, PBX1, is a member of the TALE (three-amino acid loop extension) family homeodomain transcription factors (Chang et al 1997;Merabet and Mann 2016) and well known for its functions in lymphoblastic leukemia (Kamps and Baltimore 1993;Foa et al 2000;Tesanovic et al 2014;Melendez et al 2015) and several cancers (Berge et al 2006;Qiu et al 2007;Park et al 2008;Magnani et al 2011;Thiaville et al 2012;Li et al 2014;Feng et al 2015;Jung et al 2015;Magnani et al 2015;Jung et al 2016). PBX1 also plays roles in regulating developmental gene expression (Kim et al 2002) and maintaining stemness and self-renewal (Ficara et al 2008;Jung et al 2016), and in cell-cycle progression by repressing the cell-cycle inhibitor CDKN2B to promote transition to S phase (Koss et al 2012).…”
Section: H3k36me3-associated Isoform Switch Of Pbx1 Contributes To Hementioning
confidence: 99%
“…High expression of HPIP leads to activation of some oncogenes, such as cyclin A, cyclin B, and cyclin D1 in some cell lines 7. Recent studies also demonstrated a key role of HPIP in signal transduction pathways, thereby promoting cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic pre-B cell leukemia transcription factor (PBX)-interacting protein (HPIP) is a novel oncogene that is overexpressed in various human cancers, such as non-small-cell lung cancer,4 human spinal glioblastoma,5 thyroid cancer,6 gastric cancer,7 colorectal cancer,8 breast infiltrative ductal carcinoma,9 oral carcinogenesis,10 liver cancer,11 and human melanoma cell 12. Recent studies have demonstrated the multifaceted role of HPIP in pathways associated with cancer progression, including transformation, apoptosis, invasion, and metastasis 4,6,13,14.…”
Section: Introductionmentioning
confidence: 99%